2020
DOI: 10.3390/foods9070911
|View full text |Cite
|
Sign up to set email alerts
|

A Chip Digital PCR Assay for Quantification of Common Wheat Contamination in Pasta Production Chain

Abstract: Pasta, the Italian product par excellence, is made of pure durum wheat. The use of Triticum durum derived semolina is in fact mandatory for Italian pasta, in which Triticum aestivum species is considered a contamination that must not exceed the 3% maximum level. Over the last 50 years, various electrophoretic, chemical, and immuno-chemical methods have been proposed aimed to track the possible presence of common wheat in semolina and pasta. More recently, a new generation of methods, based on DNA (Deo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Pierboni et al [ 93 ] efficiently applied droplet digital PCR to detect the presence of peanut and soybean allergens in mill and bakery products and demonstrated the usefulness of this technique for the food safety of allergic populations. More recently, Morcia et al [ 47 ] developed a duplex chip digital PCR assay able to identify and quantify common wheat presence along the whole pasta production chain. The authors found that the limit of detection of the proposed method was 0.3% common wheat contamination, whereas the limit of quantification was found at the 1.5% level.…”
Section: Molecular Approaches To Agri-food Analysismentioning
confidence: 99%
“…Pierboni et al [ 93 ] efficiently applied droplet digital PCR to detect the presence of peanut and soybean allergens in mill and bakery products and demonstrated the usefulness of this technique for the food safety of allergic populations. More recently, Morcia et al [ 47 ] developed a duplex chip digital PCR assay able to identify and quantify common wheat presence along the whole pasta production chain. The authors found that the limit of detection of the proposed method was 0.3% common wheat contamination, whereas the limit of quantification was found at the 1.5% level.…”
Section: Molecular Approaches To Agri-food Analysismentioning
confidence: 99%
“…Two genic targets for durum wheat and oat were selected from the literature or newly developed. The Grano CO2 assay, designed on TaHd1 gene sequence and developed by Morcia et al [ 18 ] was used to track Triticum genus. A new assay (Avena dig assay) was designed on actin1 gene sequence to track Avena genus.…”
Section: Resultsmentioning
confidence: 99%
“…A pillar of Italian durum wheat pasta production chain is, however, the grain identity, which is mandatory at the species level. The use of durum wheat semolina is, in fact, compulsory for Italian pasta, in which the Triticum aestivum species is considered a contamination that must not exceed the 3% maximum level [ 4 ]. However, the quality of the end products can be related not only to species, but also to the cultivar [ 5 ].…”
Section: Introductionmentioning
confidence: 99%